ZnS quantum dots and Bi metals embedded with two dimensional β-Bi2O4 nanosheets for efficient UV-visible light driven photocatalysis. (October 2021) - G., Palanisamy; K., Bhuvaneswari; T., Pazhanivel; R., Shankar; Katubi, Khadijah Mohammedsaleh; Alsaiari, Norah Salem; Ouladsmane, Mohamed
Graphical abstract: Highlights: ZnS-Bi-β-Bi2 O4 nanocomposite was prepared through wet impregnation method. Its exhibit excellent photocatalytic performance of organic dyes (MB & Rh B). ZnS/Bi/β-Bi2 O4 nanohybrid exhibit excellent reusability after 5 cycle. Abstract: In this work, the ZnS QDs, Bi/β-Bi2 O4 and ZnS/Bi/β-Bi2 O4 nanocomposite were synthesized through a facile precipitation, solvothermal and wet impregnation route respectively. The combination of bare ZnS QDs with Bi/β-Bi2 O4 nanocomposite exhibits superior photocatalytic activity against toxic pollutants (MB & Rh B) and it's attributed to the increased light-absorption capacity, efficient charge transfer process, extraordinary exciton separation, less photogenerated electron-hole recombination. The ZnS/Bi/β-Bi2 O4 nanocomposite was found to be 3 times more efficient as a photocatalyst than pristine ZnS QDs. Besides, this composite demonstrates good stability for photocatalytic activities, no substantial decomposition of activity is being observed after 5 cycle's run devoid of a main defeat in their performance. Scavenger test were also implemented in order to appreciate the possible mechanism of photodegradation. This superior photocatalytic activity and stability may offer a new sight in the improvement of a photocatalyst with large efficiency for practical application of wastewater treatment.